Concubinage or Marriage? Informal and Formal Cooperations for Innovation - Max Keilbach; Werner Bönte (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
Based on a sample of German innovating firms that contains information on formal and informal innovation cooperation between customers and suppliers, we state that firms perceive informal cooperation as being more important than formal cooperation modes. We then investigate the determinants of firms? decisions to engage into the respective cooperation modes. In line with previous empirical work, we do not find much empirical evidence for the relevance of incoming spillovers. In addition, our results suggest that this finding holds as well for informal cooper- ations. A firm?s ability to protect its proprietary innovations, however seems to be a key determinant of formal as well as informal cooperations. Furthermor absorptive capacity and the organizational structur of in-house R&D play an important role. Another relevant driver of vertical cooperations are the innovation dynamics at the industry level. Firms who operate an R&D department and firms who are involved in costly R&D projects tend to cooperate formally rather than informally.
Keywords: O32; D21; L13; O31; 330; R&D Cooperation; Spillovers; Appropriability; Innovation; Forschungskooperation; Innovation; Unternehmenskooperation; Spillover-Effekt; Wissenstransfer; Schätzung; Deutschland